[PP.22.10] EFFECTS OF ORAL VITAMIN D3 ON L-ARGININE TO ASYMMETRIC DIMETHYLARGININE RATIO IN ARTERIAL HYPERTENSION. (September 2017) - Grübler, M.; Müllner, C.; Verheyen, N.D.; Kienreich, K.; Scharnagl, H.; Trummer, C.; Schwetz, V.; Meinitzer, A.; Wetzel, J.; Pandis, M.; Gaksch, M.; März, W.; et al.
Abstract : Objective: Accumulating evidence has suggested a correlation between vitamin D (25(OH)D3) insufficiency and arterial hypertension. Vitamin D associated effects on endothelial function have been suggested to be a possible culprit, but data from clinical trials are sparse. Therefore, the present study investigated the effects of vitamin D3 treatment on L-arginine to asymmetric dimethylarginine (ADMA) ratio as a marker of endothelial function in patients with arterial hypertension and 25(OH)D3 insufficiency. Design and method: The Styrian Vitamin D Hypertension Trial is a double-blind, placebo-controlled, single-centre study conducted at the Medical University of Graz, Austria. Arterial hypertension was defined according to 24 hour blood pressure (BP) monitoring and active medication. A total of 200 study participants with arterial hypertension and 25(OH)D levels below 30 ng/mL were enrolled. The participants were randomized to receive 2800 IU of vitamin D3 per day as drops (n = 100) or placebo (n = 100) for a duration of eight weeks. The present study uses an analysis of covariance (ANCOVA) to investigate the effect of vitamin D3 treatment on L-arginine to ADMA ratio. Clinical Trials registration: EudraCT Number 2009-018125-70 ClinicalTrials.gov Identifier: NCT02136771 Results: A total of 187 participants (mean [SD] age, 60.0 [11.3] years; 47% women; 25(OH)D 21.2 [5.6] ng/mL; mean baseline systolic BP of 131.4 [8.9] mmHg; and on a median of 2 antihypertensive drugs) completed the trial. Mean treatment effect was 2.2 95%CI [−7.9 to 12.3]μmol/L/μmol/L; P = .668. In the subgroup analysis patients with a 25(OH)D concentration < 20 ng/mL (n = 73) had a significant increase in their log L-arginine to ADMA ratio (mean treatment effect 18.4 95%CI [1.84 to 34.9]μmol/L/μmol/L; P = .030). Conclusions: Vitamin D supplementation in hypertensive patients with 25(OH)D <20 ng/mL had a significant increase in their L-arginine to ADMA ratio. This supports the notion that primarily patients with 25(OH)D deficiency (<20 ng/mL) may benefit from vitamin D supplementation. Future studies should assess effects of vitamin D supplementation on endothelial function in larger samples of patients with vitamin D deficiency.